Pengaruh Translokasi t(8 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstrack Protocol Comm-ALL-92 is used for therapy ALL at Dr. Sardjito General Hospital. It is adapted from BFM Germany protocol and The ALL VINHR Protocol from the Netherlands. The outcome therapy of Comm-ALL-92 was unsuccesfull if compared to the German and Dutch. The success of chemotherapy depends on several variables namely age, sex, FAB classification, classification of desease, lymphadenopathy, Hb and leucocyte count at early stage of diagnostic and complications such as infection and bleeding. ALL is sensitive to chemotherapy, but sometimes resistant. One possible factor that cause of resistance is c-myc overexpression. Protooncogen c-myc normally involves in controling of cell growth and apoptosis. If there is chromosomal rearrangement such as translocation t (8